STRIVE : EMBRACING THE GIFT OF STRUGGLE - Fraser, Adam, Dr. (McDougall St, Milton Qld : John Wiley & Sons Australia, Ltd., 2020)
Strive shakes up everything you know about happiness, turns you around, and sets you on the track to true fulfillment. It's not what you think - happiness is not achievement and luxury and all the free time in the world. It's about working toward those things. Dr. Adam Fraser is a peak performance researcher who helps people strive for "better" in everything that they do; in this book, he shares his insights into the human condition and why happiness always feels just out of reach. Whether you're looking to boost workplace productivity, or just need the motivation to go about your daily life, this book will show you the little-known truths about happiness, purpose, and fulfillment. In working with groups from all around the world, Dr. Fraser has observed that the unhappiest people have the most comfortable jobs, making a decent living by working only a few hours per week. Some might say that sounds like paradise, but it turns out that this comfort robs them of a sense of purpose; they have nothing to strive for, because everything is fine the way it is. This book takes you inside the root of human motivation to show you how to live and work toward fulfillment.
Includes index.
Keywords: Self-actualization (Psychology).; Motivation (Psychology).; Quality of life; Work-life balance